Chromosome‐specific KASP markers for detecting Amblyopyrum muticum segments in wheat introgression lines. Issue 1 (31st January 2022) - Grewal, Surbhi; Coombes, Benedict; Joynson, Ryan; Hall, Anthony; Fellers, John; Yang, Cai‐yun; Scholefield, Duncan; Ashling, Stephen; Isaac, Peter; King, Ian P.; King, Julie
Abstract: Many wild‐relative species are being used in prebreeding programs to increase the genetic diversity of wheat ( Triticum aestivum L.). Genotyping tools such as single nucleotide polymorphism (SNP)‐based arrays and molecular markers have been widely used to characterize wheat–wild relative introgression lines. However, due to the polyploid nature of the recipient wheat genome, it is difficult to develop SNP‐based Kompetitive allele‐specific polymerase chain reaction (KASP) markers that are codominant to track the introgressions from the wild species. Previous attempts to develop KASP markers have involved both exome‐ and polymerase chain reaction (PCR)‐amplicon‐based sequencing of the wild species. But chromosome‐specific KASP assays have been hindered by homoeologous SNPs within the wheat genome. This study involved whole genome sequencing of the diploid wheat wild relative Amblyopyrum muticum (Boiss.) Eig and development of a de novo SNP discovery pipeline that generated ∼38, 000 SNPs in unique wheat genome sequences. New assays were designed to increase the density of Am. muticum polymorphic KASP markers. With a goal of one marker per 60 Mbp, 335 new KASP assays were validated as diagnostic for Am. muticum in a wheat background. Together with assays validated in previous studies, 498 well distributed chromosome‐specific markers were used to recharacterize previously genotyped wheat– Am. muticum doubled haploid (DH) introgression lines. The chromosome‐specific nature of the KASP markers allowed clarification of which wheat chromosomes were involved with recombination events or substituted with Am. muticum chromosomes and the higher density of markers allowed detection of new small introgressions in these DH lines. Core Ideas: This study involved whole genome sequencing of wheat wild relative Amblyopyrum muticum for SNP discovery with wheat. We introduce a novel methodology to generate chromosome‐specific SNPs between wheat and its wild relatives. Characterization of wheat– Amblyopyrum muticum doubled haploid introgression lines with a high‐density KASP marker were able to detect introgressions.